2017
DOI: 10.7554/elife.20552
|View full text |Cite
|
Sign up to set email alerts
|

Activity patterns of serotonin neurons underlying cognitive flexibility

Abstract: Serotonin is implicated in mood and affective disorders. However, growing evidence suggests that a core endogenous role is to promote flexible adaptation to changes in the causal structure of the environment, through behavioral inhibition and enhanced plasticity. We used long-term photometric recordings in mice to study a population of dorsal raphe serotonin neurons, whose activity we could link to normal reversal learning using pharmacogenetics. We found that these neurons are activated by both positive and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
222
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(269 citation statements)
references
References 81 publications
24
222
0
Order By: Relevance
“…However, CBF cue responses extinguished more slowly compared to VTA DA during serial value or valence reversals. This difference may highlight a selective role for ACh in extinction learning, consistent with increased perseverative responding following manipulations of CBF activity and analogous to the serotonergic system (41)(42)(43). 25 Remarkably, we found that fluctuations in CBF and VTA DA activity as well as ACh release within the BLA were correlated.…”
supporting
confidence: 58%
“…However, CBF cue responses extinguished more slowly compared to VTA DA during serial value or valence reversals. This difference may highlight a selective role for ACh in extinction learning, consistent with increased perseverative responding following manipulations of CBF activity and analogous to the serotonergic system (41)(42)(43). 25 Remarkably, we found that fluctuations in CBF and VTA DA activity as well as ACh release within the BLA were correlated.…”
supporting
confidence: 58%
“…Interestingly, we found prominent labeling in regions implicated in regulating the arousal and the affective state of the animal, including the basolateral amygdala, CA1 region of the ventral hippocampus, paraventricular (PVT), and reuneins (RE) nuclei of the thalamus, lateral supramammillary nucleus (SUMl), and serotonergic and cholinergic inputs from the dorsal raphe and basal forebrain, respectively (Hu, 2016;Reppucci & Petrovich, 2016;Swanson, 2000;Vertes, Linley, & Hoover, 2015). Many of these regions have been shown to modulate their activity in response to rewarding or aversive stimuli or to cues that predict such outcomes (Beyeler et al, 2018;Burgos-Robles et al, 2017;Hangya, Ranade, Lorenc, & Kepecs, 2015;Jimenez et al, 2018;Matias, Lottem, Dugué, & Mainen, 2017;Zhu, Wienecke, Nachtrab, & Chen, 2016). The CLA may therefore integrate some of these response features and broadcast its output to the cortex to modulate processing under emotionally salient conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of serotonin also causes sustained effects. During a reversal learning task, serotonin neurons were activated when the association pattern of cue and reward was altered . Indeed, the activation of serotonin promoted reversal learning, suggesting that serotonin enhances flexibility in learning.…”
Section: Sustained Dopamine and Serotonin Effects On Behaviormentioning
confidence: 99%
“…During a reversal learning task, serotonin neurons were activated when the association pattern of cue and reward was altered . Indeed, the activation of serotonin promoted reversal learning, suggesting that serotonin enhances flexibility in learning. In a social conditioning task, where mice showed a preference for a context where they were exposed to home cage mates, blockade of 5‐HT 1B receptor in the NAc during conditioning eliminated social preference in assessments 2 days after the conditioning .…”
Section: Sustained Dopamine and Serotonin Effects On Behaviormentioning
confidence: 99%